ANTIOXIDANT TEST OF TONER IN SKINCARE PACKAGES CIRCULATING IN INDONESIAN SOCIETY (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Toner has the function of an antioxidant because it can shrink pores and make skin fresher to ward off symptoms of premature aging. In 2021, the use of facial care or skincare products, especially toners, has greatly increased among the public based on online sales results on e-commerce (Shopee and Tokopedia). The purpose of this study was to determine the IC50 value obtained in toner in the skincare package. This study used five toner samples with 5 concentration variations (50 ppm, 100 ppm, 150 ppm, 200 ppm, 250 ppm) and measured antioxidant activity using a UV-Vis Spectrophotometer instrument with the DPPH method. The results showed that the best IC50 value was ascorbic acid (vitamin C) as a positive control with an IC50 value of 7.768 ppm and entered the very strong category. Toner 1 had an IC50 value of 62.218 ppm and was categorised as a strong antioxidant. Toner 2 had an IC50 value of 128 ppm and was categorised as a medium antioxidant. Toner 3 IC50 value of 158.972 was categorised as a weak antioxidant, and toner 4 IC50 value of 91.017 ppm is categorised as a strong antioxidant. At the same time, the one with the lowest IC50 value is toner 5, which has an IC50 value of 170.64 and is included in the weak antioxidant category. Of the five toner samples that have the best IC50 value is toner 1, with an IC50 value of 62.218 ppm.